Penguatan Pendidikan Karakter melalui Program Pengabdian Masyarakat di Desa X - Prasetyo, Hendra Dwi; Susanto, Ari; Safrezar, Burhan (PUTRA JAWA PUBLISHER, 2024)
Character education has become the main focus in facing current global challenges. Amidst the dynamics of society, community service has become an effective strategy to realize character education. This research aims to explore and analyze the impact of community service programs in strengthening character education, with a focus on Village X. The research methods used are participatory observation, interviews, and document analysis. The research results show that the community service program in Village X has successfully increased awareness of moral values, ethics, and social responsibility among the community. Additionally, this program also provides a positive contribution in developing social skills and leadership among participants, especially the younger generation. The implications of this research highlight the need for more support and collaboration between educational institutions, the government, and the community in implementing community service programs to strengthen character education.